2018
DOI: 10.2147/ptt.s161437
|View full text |Cite
|
Sign up to set email alerts
|

Limited clinical utility of HLA-Cw6 genotyping for outcome prediction in psoriasis patients under ustekinumab therapy: a monocentric, retrospective analysis

Abstract: PurposeSeveral studies have suggested that an HLA-Cw6+ allele can predict an improved outcome of treatment in psoriasis patients. The aim of the study was to assess whether the published association between HLA-Cw6 allele carriers and response to ustekinumab has the potential to impact treatment decisions.Patients and methodsDifferences in Psoriasis Activity and Severity Index 50, 75, and 90; Nail Psoriasis Severity Index; and Dermatology Life Quality Index at 16 weeks were evaluated between HLA-Cw6 allele car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…This result was demonstrated with similar or less significance by other groups with some exceptions of mixed results (5)(6)(7)(8).…”
supporting
confidence: 70%
“…This result was demonstrated with similar or less significance by other groups with some exceptions of mixed results (5)(6)(7)(8).…”
supporting
confidence: 70%
“…All studies provided data about the PASI75 response rates at 6 months (24-28 weeks) of ustekinumab treatment, and response rates were higher among HLA-C*06:02-positive patients in all included studies (Figure 2). 7,8,10,11,16,[18][19][20] Randomeffects meta-analysis revealed a pooled RD of 0.24 (95% CI, 0.14-0.35; P < .001) in favor of HLA-C*06:02-positive patients. This RD signified that if 100 HLA-C*06:02-positive and 100 HLA-C*06:02-negative patients were to be treated with ustekinumab, PASI75 would be achieved in 24 more patients in the HLA-C*06:02-positive group compared with the HLA-C*06:02-negative group.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“… 77 Notwithstanding the difference, both genotype groups had a high PASI 75 response rates, so those HLA-C*06:02 negative should not be denied treatment with ustekinumab. 77 These finding were further confirmed by a more recent retrospective study by Anzengruber et al 78 Anyway, the great heterogeneity of the included studies does not allow a generalization; 77 for this reason, the authors suggest that a personalized therapy for psoriasis patients should rely on a set of biomarkers, rather than a single one. 77 Also, the same genotype may influence response to different biologics.…”
Section: Methodsmentioning
confidence: 90%
“… 75 Anyway, the positive association between HLA-C:06:02 positivity and response to ustekinumab was questioned in more recent studies. 77 , 78 Indeed, a recent systematic review and meta-analysis of 8 studies involving 1048 psoriasis patients was run by van Vugt et al with the aim to investigate if the HLA-C*06:02 status was associated with a differential response to ustekinumab in patients affected by psoriasis. 77 They showed that HLA-C*06:02 positive patients had a median PASI75 response rate of 92% after 6 months of ustekinumab therapy compared to a median PASI75 response rate of 67% in the HLA-C*06:02 negative patients.…”
Section: Methodsmentioning
confidence: 99%